2019
DOI: 10.3390/en12081538
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fast and Energy-Efficient Direct Driven Hydraulic Actuator Unit

Abstract: In this experimental study, a Direct Driven Hydraulics (DDH) system of the closed circuit type was utilized for cyclic vertical actuation in heavy load material handling. The actuator was controlled by a speed-controlled fixed displacement pump. The high energy saving potential of this system has been demonstrated in previous studies by the authors, but the dynamic characteristics of the ramped and P-controlled base system were considered unsatisfactory. Therefore, the system was implemented with an open-loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Moreover, the dynamic characteristics of the Ramp-controlled and P-controlled base system were considered unsatisfactory. Because of this, the performance and operational characteristics of the pump speed-controlled DDH system utilizing two different motion controllers: a Pcontroller and an S-controller is present in paper [52]. It can be seen that a combination of S-curve control and hydraulic load compensation can reduce energy consumption and achieve high efficiency by the ultimate endings.…”
Section: A Review Of Eha Development Used In Engineering Machinerymentioning
confidence: 99%
“…Moreover, the dynamic characteristics of the Ramp-controlled and P-controlled base system were considered unsatisfactory. Because of this, the performance and operational characteristics of the pump speed-controlled DDH system utilizing two different motion controllers: a Pcontroller and an S-controller is present in paper [52]. It can be seen that a combination of S-curve control and hydraulic load compensation can reduce energy consumption and achieve high efficiency by the ultimate endings.…”
Section: A Review Of Eha Development Used In Engineering Machinerymentioning
confidence: 99%
“…Sebaliknya, perkembangan alat berat saat ini sangat berorientasi terhadap efisiensi energi, baik terhadap kerja sistem hidrolik maupun engine sebagai penggerak utama. Sistem hidrolik harus mampu meminimalisir kehilangan tenaga (efisien energi), serta akurat terhadap tekanan dan laju aliran dalam pergerakan actuator (rod cylinder) [4], [5]. Penggunaan fuel pada alat berat, berkaitan dengan tenaga engine yang dihasilkan juga harus efisien, dan rendah emisi [6,7,8].…”
Section: Pendahuluanunclassified
“…The authors have derived the system dynamics and concluded that the new type of P FD EM VS -EHA system has a faster dynamical response in comparison to the traditional variable speed control hydraulic system. Also, Koitto et al 154 have presented an S-curve controller DDH system where the traditional piston position control scheme is replaced by the S-curve controller. But, still, this system has some other issues such as frequency bandwidth and stiffness that require appropriate solutions.…”
Section: Different Strategies Of Energy Savingsmentioning
confidence: 99%